RESPON VARIETAS JAGUNG HIBRIDA TERHADAP NAUNGAN DAN PEMUPUKAN DI BAWAH TEGAKAN KELAPA - Husain Tabrani; Kaimuddin Kaimuddin; Syahtrianty A. Syaiful (Percetakan Umi Toaha Makassar, 2023)
The study aimed was to analyze the tolerance level of hybrid maize varieties to shading and to analyze the response to fertilization. The research was carried out in Molowahu village, Tibawa subdistrict, Gorontalo regency, Gorontalo province from August 2021 to November 2021. This study used a 2-factor factorial design with environmental design (RAK), the first factor was a hybrid corn variety consisting of three levels, namely Nasa-29, JH- 29, and Bisi-18. The second factor is the use of fertilizers, namely NPK Phonska 300 kg/ha + Urea 200 kg/ha, manure 1 ton/ha + NPK Phonska 150 kg/ha + Urea 100 kg/ha, and manure 2 tons/ha. The results of this study showed that the Nasa-29 variety showed the highest level of tolerance to shade, which was indicated by the highest production of 6.77 tons/ha. A Fertilization package of 1 ton/ha manure + Phonska NPK 150 kg/ha + Urea 100 kg/ha can increase and optimize the growth and production of corn plants in the shade between coconut plants by 0.44 tons/ha and there is no interaction between the treatment of varieties with the fertilization package.